Veiled Visions: Female Creativity, Persecution, and Oppression in Mar Gómez Glez's Fuga Mundi. Issue 4 (1st October 2020) - Pasero-O'Malley, Anthony
Abstract: This study explores how Mar Gómez Glez's play Fuga Mundi (2008) foregrounds gender issues and the oppression of women artists in order to further contemporary efforts aimed at rescuing history's forgotten female figures. Focusing on Juana de la Vega, a protagonist largely inspired by the first female professional sculptor Luisa Roldán (1652-1706), the play is set within the historical context of the Morisco expulsion from Spain. Gómez Glez employs both an all-female cast and the conventions of the historical drama to shed light on how the ramifications of gender anxieties and the persecution of minority populations based on differential notions of race and religion permeated seventeenth-century Spanish society. By drawing on metatheater, intertextual references, and the interpolation of historical documents as framing devices that juxtapose with the action of the play, Gómez Glez stimulates a critical spectatorship geared toward establishing a dialogue between dramatic fiction and historical reality.